Corporate Governance in A Service Company Using a System of Performance Indicators (Eurasian Scientific Herald, 2023)
The article deals with the issues of improving corporate governance in the service company using a system of performance indicators. The relevance of the research topic is due to the contradiction between the high economic and social significance of the problem and the underestimation of the implementation of KPI in the practice of domestic management. The author reveals the essence of the concept of “key performance indicators” and considers the point of view of researchers. As a result of the study of definitions of KPI developed by domestic authors, it was concluded that there is no single approach to the definition of this concept. The author holds the point of view that KPIs are an element of strategic management if they are subordinated to the solution of the tasks facing the enterprise. The article discusses the experience of development and implementation of the KPI system on the example of a service company. The stages and results of the process of implementation of key performance indicators are considered.